Fields and Streams : Stream Restoration, Neoliberalism, and the Future of Environmental Science - Lave, Rebecca (Book collections on Project MUSE., 2012)
Examining the science of stream restoration, Rebecca Lave argues that the neoliberal emphasis on the privatization and commercialization of knowledge has fundamentally changed the way that science is funded, organized, and viewed in the United States. Stream restoration science and practice is in a startling state. The most widely respected expert in the field, Dave Rosgen, is a private consultant with relatively little formal scientific training. Since the mid-1990s, many academic and federal agency-based scientists have denounced Rosgen as a charlatan and a hack. Despite this, Rosgen's Natur.